Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Free Cash Flow dan Profitabilitas Terhadap Kebijakan Dividen pada Perusahaan Manufaktur Go Public yang Terdaftar Di BEI (Periode 2010 – 2013) - Rosmiati Tarmizi; Tia Agnes (Universitas Bandar Lampung (UBL), 2016)
This study aims to identify the effect of managerial ownership , institutional ownership , free cash flow , and profitability on the dividend policy in the manufacturing companies go public listed on the Indonesia Stock Exchange 2010-2013 . The hypothesis was first put forward in a negative effect of managerial ownership on the dividend policy , the second hypothesis is the positive effect of institutional ownership on the dividend policy , the third hypothesis is the positive effect of free cash flow on the dividend policy , the fourth hypothesis is the positive effect of profitability on the dividend policy . Measurement of the dividend policy is based on the dividend payout ratio is seen in the company's annual financial statements . The sample in this study is that the manufacturing companies go public listed on the Indonesia Stock Exchange 2010-2013 . Sampling using purposive sampling in order to obtain a total sample of 14 manufacturing companies go public that meet the criteria of the study sample set. Managerial ownership is measured by dividing the number of shares owned by management with a total number of outstanding shares , institutional ownership is measured by dividing the number of shares owned by institutions with a total number of outstanding shares , free cash flow is measured by dividing free cash flow with total assets , profitability is measured by Return on Assets ( ROA ) . The technique of data analysis done with the classical assumption , hypothesis testing using multiple linear regression analysis using SPSS 18.0 for windows . The results showed that in partial institutional ownership , free cash flow , profitability has positive influence on the dividend policy in the manufacturing companies go public listed on the Indonesia Stock Exchange , while the variable managerial ownership negatively affects the dividend policy in the manufacturing companies go public listed on the Indonesia Stock Exchange.